Supply Chain Priority Strategy and Added Value of Jackfruit in Tambang Sub-District, Kampar District, Riau Province - Arum Rovarti Ningsih; Santosa; Azrifirwan (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
This research aimed to a) identify the flow of the jackfruit supply chain; b) obtain the added value of the jackfruit chips agroindustry; c) analyze the level of efficiency of the jackfruit chips agroindustry; d) formulate strategies and determine strategic priorities for increasing the supply chain and added value of jackfruit. The methods used in this research are both qualitative and quantitative. The research stage starts by analyzing the jackfruit supply chain using a framework of the food supply chain network (FSCN), calculating the added value of chips in the jackfruit chips agroindustry using the Hayami method and analyzing the level of efficiency of the jackfruit chips agroindustry. The researchers then formulate a strategy using SWOT and select priority strategies using the method of analytical hierarchy process (AHP). The research results showed that the supply chain structure consists of two structures, namely structure 1 (supplier-jackfruit chips agroindustry-consumer) and structure 2 (supplier-jackfruit chips agroindustry-retail-consumer). The flow of goods occurs from suppliers to consumers, the flow of money from consumers to suppliers, and the flow of information from suppliers to consumers and vice versa. The calculation of added value obtained from micro, small, and medium enterprises (SMEs) in Sinar Hidayah was IDR 8,198.71/kg, Usaha Baru Ibu was IDR 13,960.58/kg, and Restu was IDR 4,718.75/kg. The R/C ratio in SME Sinar Hidayah is 1.72, Usaha Baru Ibu is 2.42, and Restu is 1.26. Based on the results of the strategy formulation, the priority strategy was obtained, namely expanding the raw material and marketing network for jackfruit chips with a weight of 0.331, and the selected criteria was logistics with a weight of 0.322.